If we want to

minimize $f(x, y)$

subject to condition $g(x, y) = c$.

Then we treat $\lambda$ as a new variable and consider minimizing

$$h(x,y,\lambda)=f(x,y)+\lambda (g(x,y)-c)$$

Question: can we consider minimizing $u(x,y,\lambda)$?

$$u(x,y,\lambda)=f(x,y)+\lambda (g(x,y)-c)^2$$

The $\lambda$ term in $u(x,y,\lambda)$ now behaves like a potential well.

EDIT: Many thanks to Michael for spending the time to answer my question in such extraordinary details.

I actually intend to ask the following question:

minimize $f(x, y)$

subject to condition $g(x, y) = c$.

The Lagrange multiplier method requires us to consider the stationary points for $h(x,y,\lambda)$:

$$h(x,y,\lambda)=f(x,y)+\lambda (g(x,y)-c)$$

Question: can we consider the stationary points for $u(x,y,\lambda)$?

$$u(x,y,\lambda)=f(x,y)+\lambda (g(x,y)-c)^m \text { }(m=1,2,3,4,\cdots)$$

Michael's example showed that when $m=2$, we may not always have reasonable solutions. What about when $m$ is odd,like 3,5,...?


Your description of Lagrange multipliers, and of the alternative quadratic penalty method, is a bit off. Rather than jointly minimizing over $(x,y,\lambda) \in \mathbb{R}^3$, we typically want to fix $\lambda\in\mathbb{R}$ and then minimize over $(x,y) \in \mathbb{R}^2$. The solution will be parameterized by $\lambda$, so we then appropriately choose $\lambda$ to match (or approach) the desired constraint (if possible). There are conditions when this will work (details below).

Joint minimization over $(x,y,\lambda)$ is incorrect.

1) For your penalty method, minimizing $f(x,y) + \lambda(g(x,y)-c)^2$ over $(x,y,\lambda) \in \mathbb{R}^3$ leads to choosing $\lambda = 0$, and then choosing $(x,y)\in\mathbb{R}^2$ to minimize $f(x,y)$, with no regards to the desired constraint. So, this approach is wrong.

2) For Lagrange multipliers, minimizing $f(x,y) + \lambda (g(x,y)-c)$ over $(x,y,\lambda) \in \mathbb{R}^3$ is wrong. Consider $f(x,y) = x^2 + y^2$, $g(x,y) = x+y$, $c=1$. The problem of minimizing $x^2+y^2$ subject to $x+y=1$ has optimal solution $(x^*,y^*)=(1/2,1/2)$, which can be found from basic calculus. Let's see what happens with Lagrange multipliers:

Fix $\lambda$ and minimize $x^2 + y^2 + \lambda(x+y-1)$ over $(x,y)\in \mathbb{R}^2$. This leads to $x = y = -\lambda/2$. Minimizing $(-\lambda/2)^2 + (-\lambda/2)^2 + \lambda(-\lambda -1)$ over all $\lambda \in \mathbb{R}$ gives an incorrect result of $\lambda \rightarrow\infty$ and $x=y\rightarrow -\infty$. Maximizing over all $\lambda \in \mathbb{R}$ works in this particular example (due to convexity properties of the problem). Also, choosing $\lambda \in \mathbb{R}$ to satisfy the constraint $x+y=1$ gives $\lambda = -1$ and leads to the correct answer $(x,y)=(1/2,1/2)$.

A correct quadratic penalty function approach.

A correct way to implement the quadratic penalty method is to fix a large (positive) value of $\lambda$, and then choose $(x,y) \in \mathbb{R}^2$ to minimize $f(x,y) + \lambda (g(x,y)-c)^2$. The intuition is that a large $\lambda$ will heavily penalize deviation from the desired constraint $g(x,y)=c$. This is related to standard "exact penalty function" methods (just websearch that phrase). Variations on this theme are known to either work exactly and/or to converge to the optimal solution when $\lambda \rightarrow \infty$ (under certain assumptions).

Example 1:

Let's revisit the previous example with $f(x,y)=x^2+y^2$, $g(x,y)=x+y$, $c=1$, and use this quadratic penalty approach.

Fix $\lambda >0$. Minimizing $x^2+y^2 + \lambda (x+y-c)^2$ leads to $x=y=\frac{\lambda}{1+2\lambda}$. So, there is no positive value of $\lambda$ for which this method works exactly. However, as $\lambda\rightarrow \infty$ we see that the solution converges to the optimal $(x,y)\rightarrow(1/2,1/2)$. So, the intuition "works" in this particular example as $\lambda \rightarrow\infty$.

Example 2:

This example shows the quadratic penalty method does not always work. Let $f(x,y) = -(x-1)^{10}$, $g(x,y)=x^2$, $c=1$. The minimum of $-(x-1)^{10}$ subject to $x^2=1$ is $x^*=-1$. However, minimizing $-(x-1)^{10} + \lambda (x^2-1)^2$ over $x \in \mathbb{R}$ gives $x\rightarrow\infty$ for any value of $\lambda$. This gives an incorrect value of $x$ for all $\lambda$, and is also incorrect in the limit as $\lambda \rightarrow\infty$.

Proof of optimality under compactness assumptions.

Here is a proof that your quadratic penalty function will converge to an optimal solution under certain assumptions. Let $A$ be a closed and bounded subset of $\mathbb{R}^N$. Fix $c \in \mathbb{R}$. Suppose:

1) $f(x)$ and $g(x)$ are continuous functions over $x \in A$, where $x=(x_1, \ldots, x_N)$.

2) We want to minimize $f(x)$ such that $x\in A$ and $g(x)=c$. Suppose there exists a solution. Let $f^*$ be the optimal value of the objective function.

3) For each $\lambda >0$, define $x(\lambda)$ as a particular minimizer of $f(x) + \lambda (g(x)-c)^2$ over $x \in A$.


$\lim_{\lambda \rightarrow\infty} \left[f(x(\lambda)) + \lambda (g(x(\lambda)) - c)^2\right] = f^*$.
Further, for any sequence of positive values $\lambda_1< \lambda_2 < \lambda_3 < \ldots$ that satisfy $\lambda_k\rightarrow\infty$, there exists a subsequence $\lambda_{k_n}$ that satisfies $x(\lambda_{k_n})\rightarrow z^*$ for some value $z^*\in A$ that satisfies $f(z^*)=f^*$ and $g(z^*)=c$. Thus, $x(\lambda_{k_n})$ converges to an optimal solution.


Let $x^*$ be an optimal solution, so that $x^*\in A$ and $f(x^*)=f^*$, $g(x^*)=c$. Since $x(\lambda)$ minimizes $f(x) + \lambda(g(x) - c)^2$ over all $x \in A$, we know:
$f(x(\lambda)) + \lambda (g(x(\lambda)) -c)^2 \leq f(x^*)$

Furthermore, it is clear that $f(x(\lambda)) + \lambda (g(x(\lambda)) - c)^2$ is non-decreasing in $\lambda$. Thus, it must reach a finite limit as $\lambda \rightarrow\infty$, and the limit must be less than or equal to $f(x^*)$.

Now take any subsequence $\lambda_1 < \lambda_2 < \cdots$ that satisfies $\lambda_k\rightarrow\infty$. Then $\{x(\lambda_k)\}_{k=1}^{\infty}$ is an infinite sequence of values that bounce around the compact set $A$. So there must be a convergent subsequence that converges to a value $z^* \in A$ (by the Bolzano-Wierstrass theorem). With a little more work, it is not difficult to show that $g(z^*) =c$ and $f(z^*) = f^*$.

Solving $\nabla f(z) + \lambda m (g(z)-c)^{m-1} \nabla g(z)=0$.

Suppose $m \geq 1$. Searching for solutions of $\nabla f(z) + \lambda m (g(z)-c)^{m-1} \nabla g(z)=0$ can sometimes help in cases when minimizing $f(z) + \lambda(g(z)-c)^m$ over $z\in\mathbb{R}^N$ fails.


Let $f(x) = -e^{x}$, $g(x) = x^2$, $c=0$. We want to minimize $-e^{x}$ subject to $x^2=0$. The answer is trivially $x^*=0$. Let's see how the two approaches handle this.

Approach 1: Minimizing $-e^{x} + \lambda x^{2m}$ over $x \in \mathbb{R}$ leads to $x\rightarrow\infty$ whenever $\lambda \in \mathbb{R}$ and $m\geq 1$. So this approach does not work.

Approach 2: Searching for $x$ that satisfy $\frac{d}{dx}[ -e^{x} + \lambda x^{2m}]=0$ leads to:
$-e^{x} + \lambda (2m) x^{2m-1}=0$
Clearly the optimal value $x^*=0$ is not a solution to this, regardless of the value of $\lambda$ and $m$. However, there are indeed roots $x(\lambda)$ of this equation that converge to the optimal value $0$ as $\lambda \rightarrow \infty$ or $\lambda \rightarrow -\infty$. So this approach "works" in a sense.

General cases:

Consider minimizing $f(z)$ subject to $g(z) = c$, where $z=(z_1, \ldots, z_N) \in \mathbb{R}^N$ and $c\in\mathbb{R}$. Suppose $x^*$ is an optimal solution.

Typically inexact performance: Suppose $m>1$. The vector $x^*$ satisfies $g(x^*)=c$, and hence it cannot be a root of the equation $\nabla f(z) + \lambda m(g(z)-c)^{m-1}\nabla g(z)=0$ unless $\nabla f(x^*)=0$, which is often untrue. So, for any finite $\lambda$, solving $\nabla f(z) + \lambda m(g(z)-c)^{m-1}\nabla g(z)=0$ typically will not give an exact answer to the desired constrained optimization problem.

Convergence when $\lambda\rightarrow\infty$ or $\lambda \rightarrow -\infty$: Suppose $f(z)$ and $g(z)$ are differentiable, and the following conditions hold:
1) $x^*$ minimizes $f(x)$ subject to $g(x)=c$.
2) There is a $\delta>0$ such that for all $\epsilon$ that satisfy $0<\epsilon<\delta$, there are vectors $x_{\epsilon}^*$ that minimize $f(x)$ subject to $g(x)=c+\epsilon$.
3) The $x_{\epsilon}^*$ vectors satisfy $\nabla f(x_{\epsilon}^*) = \mu_{\epsilon} \nabla g(x_{\epsilon}^*)$ for some real numbers $\mu_{\epsilon}$.
4) $\lim_{\epsilon\rightarrow 0^+} x_{\epsilon}^* = x^*$ and $\lim_{\epsilon\rightarrow0^+} \mu_{\epsilon} = \mu$, where $\mu$ is a nonzero real number.

Define $\lambda_{\epsilon} = -\mu_{\epsilon}/(m \epsilon^{m-1})$. Notice that:
\begin{eqnarray} \lim_{\epsilon\rightarrow 0^+} \lambda_{\epsilon} = \infty & \mbox{if $\mu<0$}\\ \lim_{\epsilon\rightarrow 0^+} \lambda_{\epsilon} = -\infty & \mbox{if $\mu>0$} \end{eqnarray} Then it is easy to check that $x_{\epsilon}^*$ solves $\nabla f(z) + \lambda_{\epsilon} m(g(z)-c)^{m-1}\nabla g(z)=0$.

  • $\begingroup$ Michael. Thanks a lot for you answer! I added the second question in the "EDIT" part. Would you answer it for me? Best $\endgroup$ – mike Jul 16 '14 at 9:04
  • $\begingroup$ In response to your new question, I added the final section "Solving $\nabla f(x) + \lambda m (g(x)-c)^{m-1}\nabla g(x) = 0$." $\endgroup$ – Michael Jul 17 '14 at 6:08

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.